Organization of Professional Training of Communication Management and Communications Specialists - Ridei, Nataliia; Tymoshenko, Valentyna; Tytova, Nataliia; Khodunovа Victoriia; Biletska, Alona (Journal of Education, Technology and Computer Science, 2022)
The article substantiates, develops and experimentally verifies the model of the organization of professional training of communication management communications specialists in higher educational institutions in the synergy of functional and purposeful, content and methodological, organizational and technological as well as relevant subsystems. It clarifies and improves conceptual and categorical apparatus that belongs to the scientific thesaurus and vocabulary regarding information security in the field of education, science and innovation of the research apparatus. The communicative and motivational, participative and conative as well as informational and noospheric criteria have been determined. The following levels have been defined: medium, sufficient and high for the professional competence formation of communication management and communications specialists in higher educational institutions. The paper also defines educational and content modules of disciplines for communication management and communication specialists − management and educational policy, methodology of scientific research and training of professionally oriented disciplines; forms, methods and means for organizing educational and scientific as well as cognitive activity.